2010
DOI: 10.1167/iovs.09-4057
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Assessment of Mirror Artifacts in Spectral-Domain Optical Coherence Tomography

Abstract: PURPOSE. To investigate the characteristics of a spectral-domain optical coherence tomography (SD-OCT) image phenomenon known as the mirror artifact, calculate its prevalence, analyze potential risk factors, measure severity, and correlate it to spherical equivalent and central visual acuity (VA). METHODS. OCT macular cube 512 x 128 scans taken between January 2008 and February 2009 at the New England Eye Center were analyzed for the presence of mirror artifacts. Artifact severity was determined by the degree … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 26 publications
0
33
0
1
Order By: Relevance
“…Hence foveal hyporeflectivity could potentially be difficult to interpret between an image which is close to the zero delay line (which would be associated with higher reflectivity) and one which is further away (which would be less reflective). 21 In our study we avoided using reflectivity values due to this inherent difficulty in standardizing these values with a spectral domain OCT and since these signs might be specific for albinism. We also show that atypical foveal hypoplasia (seen in achromatopsia) is associated with worse visual prognosis in comparison to the typical disorders associated with foveal hypoplasia, this is due to the photoreceptor degeneration, visualized on OCT as IS/OS disruption.…”
Section: Discussionmentioning
confidence: 99%
“…Hence foveal hyporeflectivity could potentially be difficult to interpret between an image which is close to the zero delay line (which would be associated with higher reflectivity) and one which is further away (which would be less reflective). 21 In our study we avoided using reflectivity values due to this inherent difficulty in standardizing these values with a spectral domain OCT and since these signs might be specific for albinism. We also show that atypical foveal hypoplasia (seen in achromatopsia) is associated with worse visual prognosis in comparison to the typical disorders associated with foveal hypoplasia, this is due to the photoreceptor degeneration, visualized on OCT as IS/OS disruption.…”
Section: Discussionmentioning
confidence: 99%
“…At first, the region of interest (ROI) was applied to cutoff mirror artifacts in the periphery arising from the Fourier transform of the OCT fringe signal. 34 The central 5.66 mm from the horizontal dimension of the corneal diameter (x-axis) and the central 5.037 mm from the vertical dimension (y-axis) were selected as ROI from the exported image files [ Fig. 4(b)].…”
Section: Resultsmentioning
confidence: 99%
“…We have also reported the frequency of OCT scan artifacts and compared macular thickness measurements, interscan reproducibility, and interdevice agreeability across the 3 SD-OCT systems [60]. We further investigated the characteristics of a spectral-domain optical coherence tomography (SD-OCT) image phenomenon known as the mirror artifact and found that this image artifact was often associated with patients with moderate to high myopia [61]. In a separate study, we examined techniques to make TD-OCT circular scan RNFL thickness measurements comparable with those from 3D SD-OCT volumes.…”
Section: Clinical Oct Studiesmentioning
confidence: 99%